Pengaruh Peran Jender dan Stres Kerja terhadap Kinerja Perawat dengan Kepuasan Kerja sebagai Variabel Mediasi - Norasiah; Sugiati, Tinik (Jurnal Kesehatan Komunitas, 2025)
Gender roles and work stress are factors that can influence the performance of healthcare workers, particularly nurses. In a hospital setting, differences in gender roles often affect job satisfaction and performance, while work stress can be a barrier to achieving optimal performance. This study aims to analyze the influence of gender roles and work stress on nurses' performance, with job satisfaction as a mediating variable. This research adopts a quantitative approach using a survey method. Data were collected through questionnaires from 140 nurses at RSUD dr. H. Jusuf SK in North Kalimantan Province using purposive sampling. Data analysis was conducted using the Partial Least Square (PLS) method. The results show that gender roles positively affect both nurses' performance and job satisfaction, whereas work stress does not have a significant impact on performance or job satisfaction. Additionally, job satisfaction is proven to mediate the relationship between gender roles and performance but does not mediate the relationship between work stress and performance. These findings reinforce the notion that job satisfaction plays a crucial role in enhancing nurses' performance, especially in the context of gender roles. Practically, the results of this study provide implications for hospital management to develop more inclusive policies regarding gender roles and stress management strategies to improve nurses' performance. By doing so, RSUD dr. H. Jusuf SK in North Kalimantan Province can create a more supportive and conducive work environment for all healthcare workers.